Hitler and the Germans - Voegelin, Eric, 1901-1985 (Voegelin, Eric, 1901-1985. Works. 1989 ;, 1999)
Between 1933 & 1938, Eric Voegelin published four books that expressly stated his opposition to the increasingly powerful Hitler regime. As a result, he was forced to leave his homeland in 1938. Twenty years later, he returned to Germany as a professor of political science at Ludwig-Maximilian University. Voegelin's homecoming allowed him the opportunity to voice once again his opinions on the Nazi regime & its aftermath. In 1964 at the University of Munich, Voegelin gave a series of memorable lectures on what he considered "the central German experiential problem" of his time: Adolf Hitler's rise to power, the reasons for it, & its consequences for post-Nazi Germany. For Voegelin, these questions demanded a scrutiny of the mentality of individual Germans & of the order of German society during & after the Nazi period. Hitler & the Germans, published here for the first time, offers Voegelin's most extensive & detailed critique of the Hitler era. Voegelin interprets this era in terms of the basic diagnostic tools provided by the philosophy of Plato & Aristotle, Judeo-Christian culture, & contemporary German-language writers like Heimito von Doderer, Karl Kraus, Thomas Mann, & Robert Musil. His inquiry uncovers a historiography that was substantially unhistoric: a German Evangelical Church that misinterpreted the Gospel, a German Catholic Church that denied universal humanity, & a legal process enmeshed in criminal homicide. Hitler & the Germans provides a profound alternative approach to the topic of the individual German's entanglement in the Hitler regime & its continuing implications. This comprehensive reading of the Nazi period has yet to be matched.